White rice consumption and risk of esophageal cancer in Xinjiang Uyghur Autonomous Region, northwest China: a case-control study - Tang, Li; Xu, F.; Zhang, T.; Lei, J.; Binns, Colin; Lee, Andy (2015)
This study investigated the association between white rice consumption and the risk of esophageal cancer in remote northwest China, where the cancer incidence is known to be high. A case-control study was conducted during 2008-2009 in Urumqi and Shihezi, Xinjiang Uyghur Autonomous Region of China. Participants were 359 incident esophageal cancer patients and 380 hospital-based controls. Information on habitual white rice consumption was obtained by personal interview using a validated semi-quantitative food frequency questionnaire. Logistic regression analyses were performed to assess the association between white rice consumption and the esophageal cancer risk. Confounding variables including socio-demographics, family history, dietary and lifestyle factors were adjusted in the multivariate model. The esophageal cancer patients reported lower consumption levels of white rice-based products, including cooked white rice and porridge, when compared to the control group. Overall, regular consumption of white rice foods was inversely associated with the esophageal cancer risk, the adjusted OR being 0.34 (95 % CI 0.23 to 0.52) for the highest (>250 g) versus the lowest (<92 g) tertile of daily intake. Similar reductions in risk were also apparent for high consumption levels of cooked white rice and porridge. In conclusion, habitual white rice consumption was associated with a reduced risk of esophageal cancer for adults residing in northwest China. Our findings provide evidence to support the continued consumption of white rice.